2020
DOI: 10.1038/s41598-020-75811-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain morphometry in 22q11.2 deletion syndrome: an exploration of differences in cortical thickness, surface area, and their contribution to cortical volume

Abstract: 22q11.2 Deletion Syndrome (22q11.2DS) is the most common microdeletion in humans, with a heterogenous clinical presentation including medical, behavioural and psychiatric conditions. Previous neuroimaging studies examining the neuroanatomical underpinnings of 22q11.2DS show alterations in cortical volume (CV), cortical thickness (CT) and surface area (SA). The aim of this study was to identify (1) the spatially distributed networks of differences in CT and SA in 22q11.2DS compared to controls, (2) their unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…Widely decreased SA in 22q11DS compared to controls found in our analyses is in line with previous studies reporting reduced SA in 22q11DS using parcellation [ 15 ] and vertex-wise cross-sectional approaches [ 14 , 16 , 17 ]. For a detailed discussion of SA findings, see Supplementary Discussion .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Widely decreased SA in 22q11DS compared to controls found in our analyses is in line with previous studies reporting reduced SA in 22q11DS using parcellation [ 15 ] and vertex-wise cross-sectional approaches [ 14 , 16 , 17 ]. For a detailed discussion of SA findings, see Supplementary Discussion .…”
Section: Discussionsupporting
confidence: 93%
“…Syndromic individuals are typically identified very early during development and can therefore be followed up starting from childhood, providing a unique opportunity to gain insight into the neurodevelopmental mechanisms preceding the onset of psychosis. On a neuroanatomical level, studies have generally reported widespread increased CT in 22q11DS and focal decreases in posterior cingulate and superior temporal gyri (STG) compared to healthy controls [ 14 16 ], a finding that was recently confirmed in a large multisite study [ 17 ]. However, the developmental trajectory of CT in 22q11DS remains unclear [ 18 ], as some reported faster thinning [ 19 ], while others found slower thinning [ 16 , 20 ], a lack of thinning [ 15 ] or no difference in thinning [ 17 ] in 22q11DS compared to controls.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, genetic and neurodevelopmental mechanisms of antisocial behavior remain poorly understood, though GWAS have begun to identify some potential contributory factors (25)(26)(27). One factor which may play a role in variability is relative contribution to brain volume of surface area and cortical thickness, which have been shown to have separable genetic underpinnings (28) and which contribute to the neurodevelopment of volume in autism in unique ways (29,30). The group differences in mean volumes in whole brain, intracranial volume, total gray matter, and amygdala are broadly consistent with previous structural MRI literature in groups of antisocial youth and adults.…”
Section: Discussionmentioning
confidence: 99%